Metformin Inhibited GSDME to Suppress M2 Macrophage Pyroptosis and Maintain M2 Phenotype to Mitigate Cisplatin-Induced Intestinal Inflammation - Ke Jiang; Qi He; Chenhui Wang; Wen Yang; Changdong Zhou; Jian Li; Jiangbo Li; Yuke Cui; Jingqi Shi; Zhenqiao Wei; Yuanyuan Jiao; Ligai Bai; et al. (Biomedicines)
Background: The continuous clinical use of cisplatin is prevented by gastrointestinal toxicity. Methods: Cisplatin was used to treat THP-1-derived macrophages to see its differential effects on different subtypes of macrophages. Wild-type and Gsdme−/− mice models were used to examine the effect of cisplatin and metformin on intestinal inflammation in vivo. The effect of GSDME on macrophage polarization was further confirmed by GSDME knockdown. Results: We found that M2 macrophages, with more cell blebbing and GSDME cleavage, were more sensitive to cisplatin-induced pyroptosis than M1 macrophages. Cisplatin was capable of enhancing the M1 phenotype, which was reversed by GSDME knockdown. GSDME contributed to M1 polarization and GSDME knockdown promoted M2 phenotype via STAT6 activation. Reduced intestinal inflammation and increased M2 macrophage numbers was detected in cisplatin-treated GSDME-knockout mice. Furthermore, metformin alleviated cisplatin-induced intestinal inflammation by reducing M2 pyroptosis and enhancing M2 phenotype through GSDME inhibition. Conclusion: This is the first study to reveal the non-pyroptotic role of GSDME in macrophage polarization, revealing that metformin could be used in combination with cisplatin to reduce intestinal toxicity.